2020
DOI: 10.1038/s41598-020-70726-3
|View full text |Cite
|
Sign up to set email alerts
|

A biphasic nanohydroxyapatite/calcium sulphate carrier containing Rifampicin and Isoniazid for local delivery gives sustained and effective antibiotic release and prevents biofilm formation

Abstract: Long term multiple systemic antibiotics form the cornerstone in the treatment of bone and joint tuberculosis, often combined with local surgical eradication. implanted carriers for local drug delivery have recently been introduced to overcome some of the limitations associated with conventional treatment strategies. in this study, we used a calcium sulphate hemihydrate (cSH)/ nanohydroxyapatite (nHAP) based nanocement (NC) biomaterial as a void filler as well as a local delivery carrier of two standard of care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Long term multiple systemic antibiotics form the cornerstone in the treatment of bone and joint tuberculosis, often combined with local surgical eradication. These findings suggest that a biphasic ceramic based drug delivery system could be a promising alternative treatment for bone and joint tuberculosis (Qayoom et al, 2020). Indeed, bioceramics carrier systems are employed in the local delivery of growth factors, representing a promising and innovative tool in tissue engineering and dentistry.…”
Section: Biomaterials As Drugsdelivery Systemmentioning
confidence: 96%
“…Long term multiple systemic antibiotics form the cornerstone in the treatment of bone and joint tuberculosis, often combined with local surgical eradication. These findings suggest that a biphasic ceramic based drug delivery system could be a promising alternative treatment for bone and joint tuberculosis (Qayoom et al, 2020). Indeed, bioceramics carrier systems are employed in the local delivery of growth factors, representing a promising and innovative tool in tissue engineering and dentistry.…”
Section: Biomaterials As Drugsdelivery Systemmentioning
confidence: 96%
“…We have shown that NC could release around 50% of RFP in 12 weeks, thus showing sustained in vitro release unlike isoniazid (INH), which showed burst in vitro release, and around 60% of INH was released within a week. 29 The dissolution of CaS from biphasic NC with time is expected to release the drug and kill the pathogen at the bone nidus. With this dissolution of CaS, the osteoconductive nHAP will serve as a platform for neoosteogenesis by differentiating the infiltrated cells into osteoblasts and hence promote the healing of bone defect created during surgical debridement.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…27 Rifampicin alone has been reported to be more effective against methicillin-resistant Staphylococcus aureus (MRSA) redeemed from device-associated biofilm infections when compared to fusidic acid or ciprofloxacin. 28 Moreover, the interaction of rifampicin with nanohydroxyapatite as shown in our earlier study 29 allows achievement of a long-term sustained release at the infection site. Sustained local delivery of rifampicin will also prevent the emergence of drug-resistant bacteria which often precludes the effectiveness of antibiotics.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Nanotechnology-based antibiotic delivery systems offer many advantages over free antibiotics, including controlled and sustained drug release kinetics, ease of surface modification for bacteria or bone targeting, high local bioactivity, low systemic side effects, ability to deliver multiple antibiotics and, enhanced drug solubility and stability. [54,55] Some nanostructures such as metallic nanoparticles have intrinsic antibacterial activities. Qadri et al [56] utilized antibacterial activity of silvercopper-boron composite nanoparticles to eradicate Staphylococcus aureus bone infection in a mouse osteomyelitis model and demonstrated a potential inorganic route as an antibiotic free and effective alternative approach which could be used for the treatment of osteomyelitis.…”
Section: Orthopedic Infectionsmentioning
confidence: 99%